2019
DOI: 10.1021/acs.jced.9b00732
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Phenylphosphinic Acid in Supercritical Carbon Dioxide and the Influence of Methanol on the Solubility Behavior

Abstract: The solubility of phenylphosphinic acid (PPA) was measured for the first time in supercritical carbon dioxide (SCCO2) at 313, 323, and 333 K with pressure ranging from 10–20 MPa using a dynamic flow technique. The solubility of PPA in neat SCCO2 ranged from 0.1 × 10–5 to 18 × 10–5 mol/mol. The influence of cosolvent, methanol, on solubility behavior was studied by measuring the solubility of PPA in SCCO2 + methanol medium (1 and 4 mol % methanol) at 313 and 323 K with pressure varying from 10–20 MPa. The highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…It was proved that the polar solute solubility in sc-CO 2 is significantly enhanced by adding a small amount of a polar cosolvent. Remarkable effect of the addition of a little amount (less than 10%) of various kinds of polar solvents such as methanol, , ethanol, , acetone, dimethyl sulfoxide (DMSO), and menthol , on solute solubility increment in sc-CO 2 has been extensively reported, previously.…”
Section: Introductionmentioning
confidence: 95%
“…It was proved that the polar solute solubility in sc-CO 2 is significantly enhanced by adding a small amount of a polar cosolvent. Remarkable effect of the addition of a little amount (less than 10%) of various kinds of polar solvents such as methanol, , ethanol, , acetone, dimethyl sulfoxide (DMSO), and menthol , on solute solubility increment in sc-CO 2 has been extensively reported, previously.…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have demonstrated that a strategy for improving these values is by incorporating a polar or non-polar cosolvent that can increase the solvating potential of SC-CO 2 perhaps lowering the operating pressure. 15–41 A selection of some relevant studies on improving the solubility of solutes in ternary systems (SC-CO 2 + cosolvent + solute) are included in Table 1. In a recent study, Sodeifian et al found that employing menthol as a cosolvent increased the solubility of ketoconazole in SC-CO 2 at 308–338 K and 12–30 MPa from a range value between 2.00 × 10 −7 and 8.02 × 10 −5 to the drug solubility values of 1.20 × 10 −5 to 1.96 × 10 −4 .…”
Section: Introductionmentioning
confidence: 99%
“…In the current work, ethanol was used for the rst time as a cosolvent approved for pharmaceutical applications with the aim of improving the solubility of favipiravir and montelukast in SC-CO 2 and promoting further research dealing with their nanonization through techniques using SC-CO 2 as a solvent, such as rapid expansion of supercritical uid solutions (RESS). In this study ethanol was used at concentrations of 1 and 3 mol% when measuring the solubilities of favipiravir and montelukast in SC-CO 2 at various pressures and temperatures (308-338 K) (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Additionally, six density-based semiempirical models, namely; MST, 50 Sodeian-Sajadian, 51 González et al, 52 Soltani-Mazloumi, 53 Garlapati-Madras, 54 and Jouyban et al, 55 with four to seven adjustable parameters were used to correlate the solubilities of favipiravir and montelukast in both studied ternary systems.…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods for measuring solubility in SC-CO 2 . The most substantially applied by researchers to calculate the solubility of SC-CO 2 systems is using a dynamic approach (John et al 2019;Ongkasin et al 2019;Zhu et al 2016). This method is proved effective since a high number of fractionation data can be obtained in a short period.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the solubility of extract yield does not match the compound solubility of natural plant extraction. Moreover, the data on solute solubility in SC-CO 2 research are mostly based on the pure compound (Antonie and Pereira 2019;Guo et al 2019;John et al 2019;Ongkasin et al 2019). To date, no data on the solubility of SIN and ISO in SC-CO 2 extraction from cat's whiskers have been published.…”
Section: Introductionmentioning
confidence: 99%